Evaluation of Supravalvular Aortic Gradient Changes Following Inverted Y-Patch Repair - Gökmen Akkaya; Çağatay Bilen; Osman Tuncer; Yüksel Atay (Galenos Publishing House, 2020)
INTRODUCTION: This study presents our single institute experience regarding the patients who underwent surgical correction via inverted Y-patch repair with the diagnosis of supravalvular aortic stenosis. METHODS: A total of 16 patients who underwent inverted Y-patch (Doty) repair in our center between 2005 and 2019 were retrospectively analyzed. Complications, supravalvular residual gradient measurements, causes of re-operation were evaluated. RESULTS: There were 9 males, 7 females and the mean age was 41.18+-16.14 months (range: 4 months to 19 years). Eight (50%) patients were diagnosed with Williams-Beuren syndrome and 3 (18.7%) patients had a bicuspid aortic valve. Three (18.7%) patients had undergone simultaneous subaortic membrane resection and 2 (12.5%) had pulmonary patch plasty. There was one (6.7%) hospital death and no mortality was observed in the follow-up. The mean follow-up time was 5.25+-3.37 years. During this period, 2 (12.5%) patients required pulmonary balloon dilatation and one patient required repeated Doty repair and aortic valve commissurotomy two years after the initial surgery. Thereafter the same patient needed aortic homograft valve replacement and Doty repair for the third time due to severe aortic insufficiency and suprvalvular aortic stenosis. DISCUSSION AND CONCLUSION: Inverted Y-patch repair provides satisfactory results, acceptable reoperation risk, and good overall survival.